Algunos nuevos métodos pedobiológicos (1990)
The rhizosphere soil of six different plant species grown in a factorial combination with four different types of soil was analyzed to gain information about the amount of organic metabolites and their origin in the rhizosphere. Amino-acids, sugars, carbon dioxide evolution and some enzyme acti vities were estimated, The results were compared using various statistical methods such as multiple correlation, factor analysis, principal componenl analysis, and cluster analysis. The amounts of sugars, amino-acids, and the enzyme-activities of some metabolites behave in an interdependent way, suggesting a very close interrelationship with the involved organisms. While in most cases the soil was the dominating factor in the combinatinn, sometimes the plant played a major role. Some combinations suggested a very especial symbiosis of the involved organisms. Emphasis is made on the importance of such physiological investigations as a diagnostic tool for the assessment of the biological state of various natural and agricultural soils.